Women Knowledge, Attitude and Proposed Preventive Health Practices towards Menopausal Symptoms - Safaa Rashad Mahmoud; Safaa Ibrahim Ahmad; Ahmad ER. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
An alteration of lifestyle before menopause and the mode of approach to life after menopause can help those who aren’t approaching menopause to be prepared for what is ahead of them and thereby reduce the menopause-related health problems and helps them enter this stage of their life with adequate knowledge and a positive attitude. Aim: Assess women’s knowledge and attitude toward menopausal symptoms and to investigate the health proposed health practices to overcome menopausal problems. Research design: A descriptive cross- sectional study design was adopted in this study. Setting: the current study was conducted in obstetrics & gynecological outpatient clinics at Sohag University hospital in Sohag city, Egypt from April to September 2017. Sample: A convenience sampling of 390 pre-menopausal women who fit the criteria was included in the study. Tool: One tool used in the current study named as structure interview questionnaire consisting of four parts: demographic information, questions to assess knowledge, preventive health practice and attitude toward menopause. Results: Most of the women had poor level of knowledge about menopause, and less than two thirds of them (60%) had also poor level of knowledge concerning preventive health practice about menopause. Whereas (65%) of the studied women had positive attitude toward menopause. Conclusion: The study concluded that women’ knowledge level and awareness toward the preventive health practices were low with a positive attitude toward menopause. Recommendations: The study recommended that a well-informed continuous, health education program should be imparted to women. Further, emphasis also needs to be given through workshops and seminars about menopause.